Security performance analysis in wireless LANs - Nurul Anis Anati, Saripudin (2018)
The security protocol has been implemented within the network to ensure that the data sent is in integrity and security. Therefore, this experiment is to analyze the security protocol in performance of WLANs based on the IEEE 802.11 g/n standard. This experiment is conducted using a testbed to measure wireless LAN performance in terms of throughput, and average delay. It will also study the interaction between different security layers and their effect performance of congested and uncongested networks. This research will also evaluate the effect of UDP on the network performance under different security protocols.